PENDAMPINGAN DALAM PEMBENTUKAN KELOMPOK ILMIAH REMAJA (KIR) SMA NEGERI 1 BAROS, BANTEN - Aeni, Nurul; Guntara, Yudi; Ratnasari, Desi; Alfian, Iqbal; Riadah, Riadah; Asroriah, Siti; Permana, Yogi; Maharani, Anissa Listiana; Sari, Diah Permana (BEGAWE: Jurnal Pengabdian Masyarakat, 2023)
Currently, schools are competing to form extracurriculars in the field of writing, especially in the field of scientific writing such as the Youth Scientific Group. SMAN 1 Baros is one of the schools in Serang Regency that has the potential of students in the field of scientific writing. One of the places to shelter this potential is by forming extracurricular Adolescent Ilmiah Group (KIR). Students of PLP-PPLK Physics Education, Untirta, Banten collaborated with physics teachers at SMAN 1 Baros to provide assistance and the formation of the Youth Scientific Group of SMAN 1 Baros (KIBAR). In its implementation, several series of activities were carried out including socialization of KIR, registration of KIBAR members, basic training of scientific papers, research and preparation of scientific papers, and work titles. The result of this assistance is the formation of extracurricular activities of the Youth Scientific Group of SMAN 1 Baros (KIBAR) and its members have been able to make scientific papers. Then the response from the teacher council and students at SMAN 1 Baros was very positive with the establishment of this KIBAR extracurricular.